Analisis Pemanfaatan Artificial Intelligence (AI) Dalam Otomasi Administrasi Perkantoran Di PT XYZ - Mulya Salsabilla, Putrie; Wiradendi Wolor, Christian; Dewi Utari, Eka (CV. KAMPUSA AKADEMIK PUBLISING, 2025)
This study aims to explore the utilization of Artificial Intelligence (AI) in supporting office administration automation at PT XYZ, identify challenges in its implementation, and propose solutions to optimize its use. A qualitative case study approach is employed to provide an in-depth overview of AI application in document archiving and processing. The unit of analysis consists of administrative staff directly involved in using AI-based systems for daily tasks. Data were collected through observation, interviews, and documentation from relevant sources. The findings show that AI improves work efficiency, accelerates archive retrieval, and reduces manual workload. However, challenges such as limited technological understanding among users and inadequate infrastructure remain. Proposed solutions include enhancing digital literacy, providing technical training, and developing accessible, user-friendly AI systems. This study contributes to the advancement of efficient and digitally adaptive office administration systems, offering insights for organizations aiming to integrate AI in administrative processes effectively and sustainably.